Construcción de identidades en el campo médico del actual sistema de salud colombiano: una aproximación desde el análisis de campo de Pierre Bourdieu (2012)
ABSTRACT: This paper presents the possibility of addressing the issue of identity construction from the standpoint of Pierre Bourdieu’s field analysis. The question addressed in the review is “how is field theory applied to identity construction?” Initially, a brief overview of the micro/macro and action/structure integration in contemporary sociology is presented together with Bourdieu’s field theory. Then, the concept of identity is presented from the standpoint of distinguishability. Finally, and as an example, the authors discuss the application of field analysis to the theoretical and methodological approach of the medical field.